ChemInform Abstract: Efficient Preparation of Apically Substituted Diamondoid Derivatives. Issue 30 (29th July 2014) - Kahl, Paul; Tkachenko, Boryslav A.; Novikovsky, Anatoliy A.; Becker, Jonathan; Dahl, Jeremy E. P.; Carlson, Robert M. K.; Fokin, Andrey A.; Schreiner, Peter R.
Abstract An effective three‐step sequence for the synthesis of monohydroxy diamantane, triamantane, and [12]tetramantane derivatives via monosilylation of diols is presented.